2013
DOI: 10.1007/s00405-013-2626-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of quality of life outcomes in chronic rhinosinusitis after sinus surgery

Abstract: The predictive value of olfaction for quality of life (QoL) recovery after endoscopic sinus surgery (ESS) in chronic rhinosinusitis (CRS) is still underestimated. The aim of this study was to explore the proportion of patients suffering from CRS who experience clinically significant QoL improvement after ESS and identify pre-operative clinical phenotypes that best predict surgical outcomes for QoL, focusing mainly on the role of patients' olfaction. One hundred eleven patients following ESS for CRS and 48 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(86 citation statements)
references
References 27 publications
2
83
1
Order By: Relevance
“…A positive olfactory function result of ESS in CRS patients was also confirmed by a recent Greek study [7].…”
Section: Strengths and Weaknesssupporting
confidence: 62%
See 1 more Smart Citation
“…A positive olfactory function result of ESS in CRS patients was also confirmed by a recent Greek study [7].…”
Section: Strengths and Weaknesssupporting
confidence: 62%
“…ESS for patients with CRS is considered a well-established surgical method in cases where medical therapy fails [6]. Still only few studies gather the results of both quality of life measures and olfactory function after ESS in CRS patients diagnosed according to the criteria of the European Position Paper on Rhinosinusitis and Nasal Polyps (EPOS) [7,8], and no studies provide results specific for the CRSsNP subgroup.…”
Section: Introductionmentioning
confidence: 99%
“…The greatest improvement in depression-specific outcomes seems to be in those with olfactory dysfunction and nonsmokers. The impact of nasal polyps was beneficial to depression outcomes in one study of patients with CRS with nasal polyposis, 22 whereas another study found increased odds of achieving a minimal clinically important difference in patients with CRS without nasal polyposis. 17 The data that support depression-specific improvement are limited, and most studies were not designed to investigate this outcome in a comprehensive fashion.…”
Section: Impact Of Depression On Outcomesmentioning
confidence: 99%
“…17 Four studies examined depression-specific outcomes after CRSspecific medical or surgical therapy, and all found improvement in depression. 11,16,17,22 These studies aimed to determine whether treatment of CRS specifically would impact comorbid depression secondarily. Overall, there are limited data, but it seems that treatment of CRS results in a mean improvement in depression scores.…”
Section: Impact Of Depression On Outcomesmentioning
confidence: 99%
“…Results are presented by EQ-5D QoL dimension, EQ-5D index score and EQ-VAS score. Using model 1 and adjusting for demographic characteristics, we identified several categories with significant differences in the CRS participants, including mobility, usual activities, pain/discomfort, and anxiety/depression ( ported [18]. This difference in gender experience of QoL was addressed by Mendolia-Loffredo et al [19].…”
Section: Multiple Logistic Regression Analysis With Confounder Adjustmentioning
confidence: 99%